Design and Acquisition of EOG Based Interactive Communications for ALS Patients - Nese OZKAN; Ali Işık; Ugur FIDAN (International Journal of Applied Methods in Electronics and Computers, 2017)
Amyotrophic lateral sclerosis (ALS) is a motor neuron disease caused by loss of function of spinal cord and brain stem nerve cells. Loss of function in nerve cells leads to weakness and explosion (atrophy) in the muscles. The outcome of the weakness in the muscles needs the help of someone. Despite the limitations of the movement, studies on methods of increasing the daily quality of life ALS patients are continuing. Electrooculogram (EOG) signals were taken from an instrumentation amplifier with 48dB gain and 107dB CMMR ratio. A 16Hz Low Pass Filter and a 50Hz Notch Filter were used to increase the signal to noise ratio. EOG signals are digitized with 10bit resolution ADC and applied to ATmega328 microcontroller. So, the software of microcontroller determines the horizontal and vertical movements of the eye. In this way, the interactive PC software was controlled by the EOG signals. EOG-based interactive software which was developed using the C # programming language has provided to patients' daily requirements, social media accounts etc. The system has been tested on healthy subjects and it has been seen that people can control the software by eye movements. As a result, system will be useful not only for ALS patients, but also for permanent or partially bedridden patient (MS, Hemiplegia, etc.)  groups. And also, while the quality of life in the patients' own habitats is being raised, they will also be able to benefit from health services within the scope of home health services.